The Effects Of Britain’s BREXIT Decision On The Current Geopolitics Of The TRNC - Арыдемир, Х. (Journal of Oriental Studies, 2018)
The Cyprus is more than fifty years old, and the three guarantor countries are confronted as one of the most important issues between Britain, Turkey and Greece and continue to exist as a big problem despite the changing circumstances and time. Over time, the ‘Cyprus Problem’, which was carried on the International platform, has been debated again after Britain’s BREXIT decision. It is once again revealed that the strategic and geopolitical position of the Turkish Republic of Northern Cyprus (TRNC) in terms of time and the changing international conjuncture in terms of the policy of the UK has become more important. In this study, the effects of Britain’s BREXIT decision on the current geopolitics of the TRNC will be discussed.